Martin Luther King Jr.'s white moderates and moderate Baptists: Moderateness as betrayal of the gospel. (May 2019) - Hanch, Kate
In his 1963 "Letter from a Birmingham Jail, " Martin Luther King Jr. criticizes "the white moderate, " identifying them as empathizing with the Civil Rights Movement, but not acting upon it. King's "white moderate" compares to contemporary white Baptists who embody King's definition. Putting "white moderate" in conversation with "moderate Baptists" demonstrates how moderate actions betray the Gospel. Exploring the identity of the clergy whom King addresses in his letter aids in drawing out a fuller definition of "moderate." This article applies three aspects of King's critique to contemporary Baptist concerns, such as women in ministry and inclusion of LGBTQIA persons in all areas of ministry: (1) an avoidance of tension through silence, what King calls "negative peace;" (2) a sympathetic view without sustained change in social structure or policy, identified by King as "lukewarm acceptance;" and (3) using generalized statements to avoid speaking of "hot-topic" issues, which King phrases as "sanctimonious trivialities." White Baptists can fight against the trend of "moderateness" through being transformed by and participating in what King calls "direct action." In doing so, Baptists may become, to use King's term, "extremists for love."